2014
DOI: 10.1063/1.4902375
|View full text |Cite
|
Sign up to set email alerts
|

Defect structure of ultrafine MgB2 nanoparticles

Abstract: Defect structure of MgB2 bulk and ultrafine particles, synthesized by solid state reaction route, have been investigated mainly by the aid of X-band electron paramagnetic resonance spectrometer. Two different amorphous Boron (B) precursors were used for the synthesis of MgB2, namely, boron 95 (purity 95%–97%, <1.5 μm) and nanoboron (purity >98.5%, <250 nm), which revealed bulk and nanosized MgB2, respectively. Scanning and transmission electron microscopy analysis demonstrate uniform and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…4 Recently, we could confirm that the quite high content of intrinsic defects in amorphous nanoboron, as supplied by the company Pavezyum, yields MgB 2 material with unique and superior characteristics. 22 Although various MgB 2 compounds have been extensively investigated over the past decades, there is still considerable controversy about of its various properties. In particular, the defect structures of undoped and doped MgB 2 have remained unclear, especially when the crystallite or particle size is confined to nanometer dimensions.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…4 Recently, we could confirm that the quite high content of intrinsic defects in amorphous nanoboron, as supplied by the company Pavezyum, yields MgB 2 material with unique and superior characteristics. 22 Although various MgB 2 compounds have been extensively investigated over the past decades, there is still considerable controversy about of its various properties. In particular, the defect structures of undoped and doped MgB 2 have remained unclear, especially when the crystallite or particle size is confined to nanometer dimensions.…”
mentioning
confidence: 99%
“…We previously reported that a significant reduction of the average particle size of MgB 2 can be achieved by using amorphous nanoboron precursors. 22 The origin and the role of defect centers were also identified: at bulk-scale and at nano-scale, undoped MgB 2 material contains plenty of O-and Mgvacancies, respectively. 22 Although the various compound morphologies play a decisive role to control its properties, the synthesis method and doping define additional, crucial parameters that markedly impact the nature and concentration of intrinsic or extrinsic defects and the materials' electronic properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As Alpha increased, the amount of MgB 7 decreased gradually, MgB 7 were unstable phases and the phase evolution in the system was closely related to the Alpha value, and finally achieved their minimum value when Alpha increased to 2. If excess Mg were added in the reactants, the dissolved B may react with Mg to form MgB X [37][38][39][40]. In Fig.…”
Section: Formation Process Of the R-bn And H-bn In The Molten Saltmentioning
confidence: 99%
“…[30][31][32][33][34][35] On the other hand, it was suggested to enhance the structural stability of metal decorated complexes by introducing structural or chemical defects. [36][37][38][39][40][41][42] For instance, substitutional doping of boron at the carbon site in carbon nanomaterials improves dramatically the binding strength of metal atoms. 41,42 B-C mixed nanostructures have been a research focus, which are also lightweight and porous.…”
Section: Introductionmentioning
confidence: 99%